The Use of PowerPoint in Supporting Arabic Language Learning with the ABY Textbook at Ma'had Hidayatullah Kota Batu - faqih zaenal abidin (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
This study aims to evaluate the effectiveness of integrating PowerPoint media with the textbook al-‘Arabiyyah Bayna Yadayk (ABY) in Arabic language instruction at Ma’had Hidayatullah Kota Batu. It employs a qualitative descriptive method with a case study approach. Based on classroom observations, PowerPoint has been found to enhance the delivery of ABY material through visual support such as illustrations, audio elements, and structured dialogues, facilitating the understanding of vocabulary, sentence structures, and communicative contexts. Interactive slides and contextual images also boost student motivation and engagement. Learner responses indicate that this multimedia approach improves comprehension and retention, making the learning process more dynamic and engaging. Theoretically, the study draws on Mayer’s Multimedia Learning theory and the communicative approach to language teaching, which emphasizes practical language use in real-life contexts. Although there are technical challenges, such as dependency on electronic devices and limitations in summarizing long texts, PowerPoint proves effective in fostering active participation and language competence. The study recommends teacher training and the strengthening of technological infrastructure as strategic steps to improve the quality of language learning in Islamic boarding school settings.